Animating English Fluency: Empowering Senior High Students Through Speaking Activities with Animated Series - Daffa Imam Fadilla; Mutiarani Mutiarani (Jurnal Studi Guru dan Pembelajaran, 2024)
Effective communication necessitates discussions about the topic at hand, highlighting the significance of speaking skills. Proficiency in speaking significantly impacts one's character, requiring consistent practice to refine sentence structure and pronunciation. Leveraging practice methods, such as utilizing media like animation series, contributes significantly to honing speaking abilities. While grammar is often overlooked in everyday conversation, the essence lies in mutual understanding during dialogues. Vocabulary acquisition, mainly through regular reading, notably aids language fluency, especially in foreign languages. A teacher's role extends beyond content delivery to understanding the learning context and methods, encouraging students to apply what they've learned. Fostering self-confidence in students, particularly during the transition from junior to senior high school, is pivotal in teaching language skills. Integrating reading and listening into speaking lessons enriches vocabulary and enhances comprehension skills indispensable for effective communication. This study demonstrates the importance of effective communication as individuals convey information or messages during conversations. The focus is on emphasizing the necessity for teachers to prioritize enhancing speaking skills among students in classrooms. Improving students' proficiency in foreign languages is crucial, and it is intertwined with the utilization of appropriate media.